Expression and Anticoagulant Function of the Endothelial Cell Protein C Receptor (EPCR) in Cancer Cell Lines - Tsuneyoshi, Naoko; Fukudome, Kenji; Horiguchi, Shin-ichiro; Ye, Xiaofen; Matsuzaki, Miwako; Toi, Masakazu; Suzuki, Koji; Kimoto, Masao (Thrombosis and Haemostasis, 2001)
Induction of procoagulant factors in malignant cells is considered to be the major cause of coagulation disorders in cancer. Thrombomodulin (TM), a negative regulator of coagulation was also found to be expressed in cancer cells. We report here evidence for another anticoagulant, the endothelial cell protein C receptor (EPCR), in cancer cells. EPCR was detected in several cell lines derived from various types of cancer. Significant levels of protein C (PC) activation were detected only with cell lines expressed both EPCR and TM. Anti-EPCR monoclonal antibodies (mAbs) specifically inhibited the activation. Thus, EPCR function appears to be important for PC activation by cancer cells. In addition, we detected EPCR expression in tumor cells from breast cancer patients, with an extremely high frequency. EPCR function may contribute to progression or pathogenesis of some types of cancer, and may explain the complexity of coagulopathy in cancer patients.
Keywords: Protein C; endothelial cell; receptor; glioblastoma; leukemia